Exploring the relationship between physical activity and cognitive function: an fMRI pilot study in young and older adults - Feng, Jie; Song, Huiqi; Wang, Yingying; Zhou, Qichen; Zhou, Chenglin; Jin, Jing (Frontiers in Public Health, 2024)
Background: There are limited studies exploring the relationship between physical activity (PA), cognitive function, and the brain processing characteristics in healthy older adults. Methods: A total of 41 participants (42.7 ± 20.5 years, 56.1% males) were included in the data analysis. The International Physical Activity Questionnaire Short Form was used to assess PA levels, and the Chinese version of the Montreal Cognitive Assessment-Basic and the Flanker task were employed to evaluate cognitive function. Furthermore, fMRI technology was utilized to examine brain activation patterns. Results: The cognitive function of the older adults was found to be significantly lower compared to the young adults. Within the older adults, those with high levels of PA exhibited significantly higher cognitive function than those with low and medium PA levels. The fMRI data showed significant differences in brain activation patterns among young adults across the different PA levels. However, such difference was not observed among older adults. Conclusions: A decline in cognitive function was observed among older adults. There was a significant correlation between the levels of PA and cognitive function in healthy elderly individuals. The study demonstrated significant effects of PA levels on brain activation patterns in inhibitory control-related regions among young adults, while not significant among older adults. The findings suggest that neurological mechanisms driving the relationship between PA and cognitive function may differ between older and young adults.